Installation impact on pusher CROR engine low speed performance and noise emission characteristics. (1st January 2012) - Stuermer, A.; Yin, Jianping
The renewed interest in the contra-rotating open rotor (CROR) as a potential highly efficient powerplant for future transport aircraft has prompted a study into the aerodynamic and aeroacoustic performance of this type of engine at DLR. With significant technical challenges related to the noise emissions and installation effects remaining to be addressed prior to realisation of a viable engine of this type, a study of a generic pusher-configuration CROR propulsion system is presented, which focuses on the impact of installation effects on the rotor aerodynamics and noise emissions. The two primary installation effects angle of attack and the pylon wake are studied utilising a high-fidelity coupled analysis based on unsteady Reynolds averaged Navier-Stokes (uRANS) simulations with the CFD solver TAU and the aeroacoustic analysis tool APSIM, both developed at DLR, highlighting the importance of these aspects on CROR in-plane loads and rotor noise emissions.